Bioenergy recovery from methanogenic co-digestion of food waste and sewage sludge by a high-solid anaerobic membrane bioreactor (AnMBR): mass balance and energy potential. (April 2021) - Cheng, Hui; Li, Yemei; Hu, Yisong; Guo, Guangze; Cong, Ming; Xiao, Benyi; Li, Yu-You
Graphical abstract: Highlights: Biogas yield was upgraded by co-digestion sludge with food waste in the AnMBR. Net energy balance was achieved at all FW/SeS ratios in the high-solid AnMBR. EROI increased from 3.53 to 7.48 with FW ratio increased from 0 to 100%. The relationship between net energy balance and C/N ratio was firstly established. The sigmoid-type function is capable of predicting net energy regardless of region. Abstract: To support smart city in terms of municipal waste management and bioenergy recovery, a high-solid anaerobic membrane bioreactor (AnMBR) was developed for sewage sludge (SeS) and food waste (FW) treatment in this study. COD mass balance showed that 54.1%, 66.9%, 73.5%, 91.4% and 93.5% of the COD input was converted into methane at the FW ratio of 0, 25%, 50%, 75% and 100%, respectively. The corresponding net energy balance was 13.6, 14.1, 17.1, 22.9 and 27.4 kJ/g-VS, respectively. An important finding of this investigation was that, for the first time, the relationship between net energy balance and carbon to nitrogen (C/N) ratio was revealed and the established sigmoid-type function was shown to be capable of predicting energy balance at different C/N ratios regardless of the region. The outcomes of this study show the potential of high-solid AnMBRs in SeS and FW treatment for supporting smart cities in the future.